INCAPACIDADE FUNCIONAL DA COLUNA CERVICAL EM ESTUDANTES UNIVERSITÁRIOS COM DOR CERVICAL CRÔNICA - DE SOUSA LIMA, AMANDA; SIQUEIRA DINIZ , INGRYD IOLANDA; MACEDO, MICHELE APARECIDA; AUDINA SOARES ROSA, RAFAELA; VENTURINI, CLAUDIA (Sinapse Múltipla, 2019)